Neostijlen en eclecticisme : van het Justitiepaleis to de Cogels-Osylei - Bral, Guido Jan, 1953-; Verpoest, Luc, 1945- (Tielt : Lannoo, 2008)
Gent, Brussel, Schaarbeek, Luik, Laken, Loppem, Antwerpen, Dadizele, Spa, Sint-Amandsberg, Fauls-les-Tombes - Spa, Sint-Gillis, Bugenhout, Borgerhout, Brugge, Strépy-Bracquegnies, Mechelen, Tervuren, Oostende, Gent, Antwerpen, Brussel